Karakteristik Sensori dan Kimia Mochi dengan Substitusi Tepung Kulit Pisang Kepok (Musa acuminate L.) - Muhammad Fakih Kurniawan; Titi Rohmayanti; Siti Nova Isda Dwiyanti (Food Scientia : Journal of Food Science and Technology, 2023)
Mochi cake is a typical West Java souvenir product made from glutinous rice flour. Flour from banana peels has the potential to substitute flour to make mochi. This research aims to make mochi using glutinous rice flour which is substituted with kepok banana peel flour. Completely Randomized Design (CRD) was used in this study consisting of one factor, namely the ratio of glutinous rice flour and kepok banana peel flour (100%: 0%), (90%: 10%), (80%: 20%), (70%: 30%). The mochi products were analyzed for sensory and hedonic quality to selected product. Proximate tests were carried out for these selected products. The selected mochi product (80%:20%) has a dark brown color, a banana-like aroma and taste, and a chewy texture. Panelists gave favorable scores for taste, aroma, and texture parameters, but expressed a dislike for the color of the selected mochi. Selected mochi chemical content composed of 0.24% ash content; 8.71% protein; 45.69% carbohydrates; 3.15% fat content; and 42.21% water content. For fat and water content, it does not meet Indonesian National Standard  of cake (SNI 01-4309-1996). Therefore, banana peel flour has the potential to be an ingredient for making mochi. in the future, it needs to be reformulated so that the water and fat content meets the standard and have a better color quality.